Color Evaluation of Dry Vermicelli Made from Combination of Arenga Starch, Rice Flour and Sorghum - Febiani Dwi Utari; Ririn Puji Hastuti; Setia Budi Sasongko; Mohamad Djaeni (Diponegoro University, 2022)
In Indonesia, vermicelli is usually produced using arenga starch. But the arenga starch has limited in the term of quantity and the nutritional quality. In order to improve the arenga starch vermicelli, the formulation was combined with rice flour and sorghum. Each single change in vermicelli formulation will be modifies the final product color. This research studied the effect of vermicelli formulation on the color change of dry vermicelli. During the production of vermicelli, arenga starch was mixed with 10-90% of rice flour. The color parameter was observed as L* (lightness), a* (redness and greenness), and b* (yellowness and blueness). The total color difference was also calculated. The procedure was repeated with addition of sorghum. Result showed that the addition of rice flour increased the L* value. Meanwhile, the addition of sorghum decreased the L* value. Total color difference was higher in addition of sorghum.